Half-dose fingolimod for treating relapsing-remitting multiple sclerosis: Observational study. (February 2018) - Zecca, Chiara; Merlini, Arianna; Disanto, Giulio; Rodegher, Mariaemma; Panicari, Letizia; Romeo, Marzia Anita Lucia; Candrian, Ursula; Messina, Maria Josè; Pravatà, Emanuele; Moiola, Lucia; Stefanin, Catia; Ghezzi, Angelo; et al.
Objectives: To investigate the efficacy and safety of fingolimod (FTY) 0.5 mg administered every other day (FTY-EOD) compared to every day (FTY-ED) in multiple sclerosis patients. Methods: Multicentre retrospective observational study. Clinical, laboratory and neuroimaging data were consecutively collected from 60 FTY-EOD and 63 FTY-ED patients. Baseline characteristics were compared using logistic regression. Efficacy in preventing occurrence of relapses and demyelinating lesions was tested using propensity score–adjusted Cox and linear regressions. Results: Weight was inversely associated with risk of switch to FTY-EOD because of any reason (odds ratio (OR) = 0.94, 95% confidence interval (95% CI) = 0.89–0.99, p  = 0.026), and female sex and lower baseline lymphocyte count were positively associated with switch because of lymphopenia. Compared to FTY-ED patients, FTY-EOD patients were at higher risk of developing relapses (hazard ratio (HR) = 2.98, 95% CI = 1.07–8.27, p   =  0.036) and either relapses or new magnetic resonance imaging (MRI) demyelinating lesions (combined outcome, HR = 2.07, 95% CI = 1.06–4.08, p   =  0.034). Within FTY-EOD, treatment with natalizumab before FTY and lower age were positively associated with risk of developing relapses and combined outcome, respectively (HR = 25.71, 95% CI = 3.03–217.57, p  = 0.002 and HR = 0.85, 95% CI = 0.77–0.96, p   =  0.005). FTY-EOD was overall well tolerated. Conclusion: Disease reactivation was observed in a significant proportion of patients treated with FTY-EOD. Neurologists should be cautious when reducing FTY administration to every other day, especially in younger patients and those previously treated with natalizumab.